Need Assesment of English E-Module Integrated to Islamic Value Development for the Eight Grade Students at Islamic Schools - Iful Rahmawati Mega; Winda Purnama Sari (Universitas Cokroaminoto Palopo, 2021)
This paper describes the results of need analysis of the eighth-grade students of Islamic Schools in Pangkalpinang, Bangka Belitung province, pointed on the development of English E-Module (electronic module) integrated to Islamic value which aims to acknowledge the needs of English E-Module integrated with Islamic value development for junior high schools students. The data were collected using a questionnaire with four aspects: 1) Interest in Learning English integrated in Islamic value, 2) Media to support students’ learning, 3) Pedagogy, textbooks, and learning media, 4) Media-based independent learning. This study was conducted on the 44 students of Islamic junior high schools in Kota Pangkalpinang. Based on the analysis, it reveals that 1) 64.40% of students are interested in learning English, 2) 59.09% of students need media to support their learning, 3) 81.82% of students need pedagogy, textbooks, and learning media, 4) 55.30% students need media-based independent learning. These findings must offer as a framework for the development of the English E-Module integrated to Islamic value for the Eighth-grade students of Islamic schools in Kota Pangkalpinang.